2010
DOI: 10.1177/0165025410380983
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Jalan Sesama on the educational and healthy development of Indonesian preschool children: An experimental study

Abstract: Jalan Sesama was developed to address the developmental needs of Indonesian children ages 3 to 6 years. Using a randomized experimental research study design, this study examined the effect of a 14-week intervention on 160 children in the Pandeglang District in Indonesia’s Banten Province. Results offer solid evidence that early cognitive skills, literacy, mathematics, health and safety knowledge, social development, environmental awareness, and cultural awareness significantly improved from baseline to post-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…This measure, which has been successfully used with preschool-aged children in other countries, 17,18 involved children who provided characters' exact names. Researchers presented participants with a picture card featuring 12 current and popular characters (5 domestic, 5 international, and 2 foils).…”
Section: Media Exposurementioning
confidence: 99%
“…This measure, which has been successfully used with preschool-aged children in other countries, 17,18 involved children who provided characters' exact names. Researchers presented participants with a picture card featuring 12 current and popular characters (5 domestic, 5 international, and 2 foils).…”
Section: Media Exposurementioning
confidence: 99%
“…Some existing research has explored the use of specific educational media content in the classroom. Studies have shown positive impacts of classroom technology and media interventions on literacy (Penuel et al, 2012), vocabulary (Dore et al, 2019), math (Schacter et al, 2016;McCarthy et al, 2018), computational thinking (Portelance et al, 2016), English language learning (Michael Cohen Group, 2013) and health and safety knowledge (Borzekowski and Henry, 2010) during preschool. Based on these and similar findings, experts have argued that educational media could be beneficial for learning in preschool settings (Pasnik et al, 2016) and have called for better models to understand its appropriate use (Daugherty et al, 2014).…”
Section: Purposes and Contexts Of Classroom Media Usementioning
confidence: 99%
“…Two educational television studies, Baydar et al (2008) and Borzekowski and Henry (2011), met the criteria for inclusion in the review. However, neither study provided the summary statistics needed to compute effect sizes.…”
Section: Effects Of Educational Televisionmentioning
confidence: 99%
“…However, neither study provided the summary statistics needed to compute effect sizes. Borzekowski and Henry (2011) randomly assigned children to three levels of exposure to Jalan Sesama: control, low, and high. The highexposure group watched three to four episodes of the target program over a 14 week period, while the low-exposure group watched one episode a week over 14 weeks.…”
Section: Effects Of Educational Televisionmentioning
confidence: 99%